Influence of Internal Scrap on Mechanical Properties of Selected Cobalt Alloys - Dęsoł, Bartosz; Zapała, Renata; Pałka, Paweł (Journal of Casting & Materials Engineering, 2017)
This paper presents the results of mechanical tests carried out on two different commercially available cobalt alloys applied indental prosthetics for the production of frame dentures. The test samples were obtained by the method of investment casting using as a charge pure primary materials and pure primary materials mixed with various additions of process scrap (25, 50, and 75%). The tests showed that the alloys could not reach the mechanical properties reported by the manufacturer in either case. In the case of the alloy without the addition of tantalum, the general conclusion was that both the plastic and strength properties decreased with increasing amounts of the introduced process scrap. The mechanical properties (mainly elongation) of the alloy containing Ta reached the highest values in the samples containing 75% of the process scrap. Examinations of fractures carried out by SEM have revealed their varied character – ductile or transcrystalline. All of the samples tested showed the presence of dendrites and solidification areas, with shrinkage porosity occurring in the internal sample zones.